The Influence of English College Students’ Learning Environment and Self-Directed Learning on Their Academic Achievement - Syafiqurrakhman, M Amien; Basikin, Basikin; Nisa, Liana Buruuja (STKIP Singkawang, 2024)
The current research aims to investigate the influence of English Language Education Department students’ learning environment and self-directed learning towards their academic achievement. Moreover, it also investigates how the students’ learning environment, self-directed learning, and academic achievement scores differ by their educational level. This research was an ex post facto research design. The participants involved in the current research were 106 consisted of 73 undergraduate students and 33 graduate students of the English Language Education Department at Yogyakarta State University. They were selected based on convenience sampling. This research adopted two instruments namely EFL Learning Environment Questionnaire (QEFL-LE) developed by Mutlu (2017) and Self-Directed Learning Scale (SDLS) questionnaire from Lounsbury et al. (2009). Before carrying out the investigation, a pilot study was conducted to improve the validity and reliability of the instruments. Furthermore, composite questionnaires were distributed, resulting in three quantitative data sets of students’ learning environment, self-directed learning, and academic achievement. Finally, both descriptive and inferential statistics were performed using IBM SPSS to analyze the data. The findings reported that there were significant differences in the students’ scores in learning environment, self-directed learning, and academic achievement based on their educational level (bachelor’s and master’s degree). In addition, the scores of master’s degree students consistently surpassed those of bachelor’s degree students in every variable in the current research. Furthermore, it confirms that students’ academic achievement was significantly influenced by their learning environment and self-directed learning. Moreover, students’ learning environment and self-directed are simultaneously become the best predictor of their academic achievement. Based on these findings, pedagogical implications are suggested for English teaching and learning in a higher education context